Monitoring profilov ťažkých kovov v matriciach liečivých rastlín, liekov a homeopatických prípravkov z radu antitusík rádionuklidovou röntgenofluorescenčnou spektrometriou - Lukačovičová, Oľga; Mikuš, Peter (Chemické listy, 2018)
Reliable, fast, simple and low-cost analytical procedure based on radionuclide X-ray fluorescence spectrometry (RRFS) was proposed to identify and determine heavy metals in various antitussive preparations of synthetic and biological origin. Various materials (tablet dosage forms, granules, plants) can be analyzed directly without the need of isolation of the analyzed compounds from their matrices so that errors in the analytical process are minimized. External matrices, such as Medicago sativa L. , benzoic acid, and dextran were proposed to quantify heavy metals in some problematic materials ( Farfarereae folium , effervescent tablets of medicine ACC long, hard capsules of various homeopathics, respectively) that had not allowed homogeneous implementation of standard addition of analyzed elements into the standardized tablet forms used for the RRFS analysis. The appropriate external matrices were consistent with the original ones in terms of matrix effects (e.g., background noise produced and approximate levels of naturally occurring heavy metals studied), and they allowed to prepare well defined tablets including required amounts of the standard additions of heavy metals providing proper calibration parameters. The RRFS method applied for the original or external matrices enabled an effective and economic control of antitussive preparations for selected heavy metals contents evaluated according to the established directives and laws. Hence, it is recommended for a routine use in quality control laboratories.
Keywords: Plants, Medicinal; těžké kovy; fluorescenční spektrometrie; léčivé rostliny; Plant Extracts; Antitussive Agents; kontrola léčiv a omamných látek; rostlinné extrakty; antitusika; Drug Contamination; Drug and Narcotic Control; Spectrometry, Fluorescence; Metals, Heavy; kontaminace léku